EFEKTIVITAS PROGRAM BIMBINGAN PERKAWINAN DI KOTA SAMARINDA - Firmansyah; Andaryuni, Lilik (The Juris, 2023)
Research on the Effectiveness of Pre-Marital Counseling Programs in Samarinda City through field research methods delineates the pivotal role of this program in preparing prospective couples for marriage and establishing a harmonious family. The research conducted in Samarinda City allowed for data collection from pre-marital counselors and prospective couples who participated in this program. The results indicate the program's success in enhancing the physical, mental, and spiritual readiness of prospective couples. Various teaching methods such as lectures, group discussions, case simulations, and personal counseling sessions provide in-depth insights into various aspects of marriage, practical skills, and relevant spiritual values. However, the evaluation identified several challenges that need addressing, such as improving program accessibility, ensuring consistent implementation, accommodating diverse group needs, and ongoing evaluations. Nonetheless, the pre-marital counseling program in Samarinda City significantly contributes to comprehensively preparing prospective couples, including in knowledge, skills, and legal preparations. Thus, this study underscores the importance of ongoing evaluation and program adaptation to enhance its effectiveness. This supports the development of a more responsive and inclusive program, offering greater benefits to prospective couples as they prepare for married life.